2023
DOI: 10.3390/ijms24065167
|View full text |Cite
|
Sign up to set email alerts
|

Pillararenes as Promising Carriers for Drug Delivery

Abstract: Since their discovery in 2008 by N. Ogoshi and co-authors, pillararenes (PAs) have become popular hosts for molecular recognition and supramolecular chemistry, as well as other practical applications. The most useful property of these fascinating macrocycles is their ability to accommodate reversibly guest molecules of various kinds, including drugs or drug-like molecules, in their highly ordered rigid cavity. The last two features of pillararenes are widely used in various pillararene-based molecular devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…PAs have been investigated as novel and popular hosts for various applications. 126–128 Zhang et al have reported a hybrid supramolecular PS based on water soluble sodium carboxylato pillar[5]arene (SP[5]A) and 5-carboxypentyl-triphenylphosphonium bromide stabilized on AuNPs for use in pH-activated PDT (Fig. 17).…”
Section: Supramolecular Assemblies For Drug Delivery and Pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…PAs have been investigated as novel and popular hosts for various applications. 126–128 Zhang et al have reported a hybrid supramolecular PS based on water soluble sodium carboxylato pillar[5]arene (SP[5]A) and 5-carboxypentyl-triphenylphosphonium bromide stabilized on AuNPs for use in pH-activated PDT (Fig. 17).…”
Section: Supramolecular Assemblies For Drug Delivery and Pdtmentioning
confidence: 99%
“…PAs have been investigated as novel and popular hosts for various applications. [126][127][128] Zhang et al…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…28,31−34 Subsequently, the concept of photoresponsive pillar [5]arene has been further extended to construct various forms of amphiphilic carriers. 17,35 For example, Yang and Huang individually prepared supramolecular amphiphiles from a water-soluble pillar [6]arene and the hydrophobic azobenzene threads and applied them in the photo-induced controlled release. 31,32 In addition, Tong and co-workers utilized the polymer functionalized azobenzene thread complexed with a water-soluble pillar [6]arene to prepare photoresponsive vesicles for drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In photoresponsive supramolecular systems, azobenzene is a widely recognized molecular motif that demonstrates reversible photoisomerization between trans and cis configurations when exposed to light with a specific wavelength depending on the types of the azobenzene. Generally, only target guests with the most suitable size and shape can be stabilized within the binding cavity of the macrocyclic hosts via convergence of multiple noncovalent interactions. Therefore, significant changes in shape, size, and polarity of the azobenzene upon photo-induced isomerization can result in switchable binding affinities toward the host molecules. In 2011, Stoddart and co-workers pioneered the synthesis of an azobenzene substituted pillar[5]­arene and employed the photoisomerization reaction for the controllable molecular self-assembly. , When azobenzene is in the trans configuration, it is encapsulated within a pillar­[ n ]­arene cavity to form a more stable inclusion complex due to its extended conformation, whereas the cis isomer becomes more contracted in size, resulting in the destabilization of the host–guest complex and the release of the guest molecule from the cavity. , Subsequently, the concept of photoresponsive pillar[5]­arene has been further extended to construct various forms of amphiphilic carriers. , For example, Yang and Huang individually prepared supramolecular amphiphiles from a water-soluble pillar[6]­arene and the hydrophobic azobenzene threads and applied them in the photo-induced controlled release. , In addition, Tong and co-workers utilized the polymer functionalized azobenzene thread complexed with a water-soluble pillar[6]­arene to prepare photoresponsive vesicles for drug delivery . To the best of our knowledge, photo-induced drug delivery based on azobenzene and pillar[5]­arene has only been studied in the amphiphilic system.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we focus on the progress of pillararenes in biological applications, especially as antimicrobial agents. Considering that there have been some excellent reviews available on drug delivery systems (DDSs) based on pillararenes, 24,25 the complexation of antibiotics by host–guest interaction alone will not be discussed here.…”
Section: Introductionmentioning
confidence: 99%